Innovation technologique et pratiques domestiques : analyse d'une expérience domotique - Beillan, Véronique (Sociétés contemporaines, 1994)
À partir du suivi sociologique d'une expérience domotique portant sur quinze logements du secteur HLM, cette étude traite des conditions d'appropriation sociale d'une nouvelle technologie domestique. Après un exposé de la méthode de recueil des données, basée sur la réalisation de trois vagues ď entretiens - réparties sur trois ans - auprès des ménages du lotissement domotique, l'article présente les premiers résultats ainsi que les nouvelles pistes de recherche à approfondir lors de la troisième et dernière phase du suivi. L'analyse comparative des deux premières vagues d'entretiens a permis de noter la permanence des attentes et des attitudes des ménages à l'égard de la domotique mais aussi le caractère hétérogène et ambivalent de ces dernières. Des freins ď ordre socio-économique et socio-culturel à l'intégration sociale de la technique ont été identifiés. Ainsi, des liens se dessinent entre l'automatisation des tâches et certains éléments tels que le statut et l'identité de la femme, l'organisation et la hiérarchisation des activités domestiques, les pratiques de délégation et ď externalisation du travail domestique.
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; care; cours; discipline; europe; france; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Love and Intimacy: The Gender Division of Emotion and 'Emotion Work': A Neglected Aspect of Sociological Discussion of Heterosexual Relationships - Duncombe, Jean; Marsden, Dennis (Sociology, 1993)
This paper discusses the role of ideologies of love and intimacy in heterosexual coupledom, and examines the applicability of theories of the gender division of 'emotion work' to the field of intimate personal relationships. Research on the private sphere of the family has recently focused on quantifying instrumental aspects of relationships, such as financial management, the domestic division of labour and informal care. However, although fruitful, such approaches neglect the expressive or emotional; particularly the experiences of love and intimacy, which many people say they regard as a key element in their personal relationships. We suggest reasons for British sociology's neglect of what is almost a cliche in everyday discourse. And we present evidence (including preliminary findings from our own research on heterosexual couples) that - despite dissatisfaction with gender inequalities in domestic tasks and finance - many women express unhappiness primarily with what they perceive as men's unwillingness or incapacity to `do' the emotional intimacy which appears to them necessary to sustain close heterosexual couple relationships. We illustrate how similar discussions of gender differences in emotional behaviour have emerged elsewhere (including in the new masculinity literature), raising questions about how far men's and women's emotional behaviour can and should change.; The exploration of socially-regulated or `managed' gender divisions in intimate emotional behaviour entails two related but distinct questions: are men and women equally `susceptible' to the emotions or discourses of love and intimacy; and, do they handle such emotions in similar ways in the context of close personal relationships. We suggest how research findings on heterosexual couple relationships can be linked to work on the social regulation of emotion, which argues that there is a `gender division of emotion work' where it is assumed that women will take responsibility for the management of emotion in the private sphere.
Keywords: 1900-1999; 1980-1989; angleterre; approches et analyses; care; cours; discipline; emotional labor; europe; hétérosexualité; postmodernisme; premier cycle; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; thématiques; travail